ACute toxicity of m-cresol on the fry rainbow trout (Oncorhynchus mykiss walbaum, 1792) - Saglam, N; Ural, MS (Parlar Scientific Publications (P S P), 2005)
In this study, the acute toxicity of m-cresol on fry rainbow trout, Oncorhynchus mykiss, was investigated. Liquid m-cresol (C7H8O) was applied at concentrations of 1, 2, 3, 4, 5, 6, 7, 8, 10, 16, and 32 ppm in 80-L aquariums with micropipette. Temperature, pH and dissolved oxygen of aquarium water were also measured and for each treatment, three replicates and control groups were used. The statistical acute toxicity bioassay was performed to determine the lethal concentrations, (LC10, LC50 and LC90 values) and lethal times (LT10, LT50 and LT90 hours) of m-cresol after 24, 48, 72 and 96 h. No mortalities were observed at the concentrations of 1, 2, and 3 ppm. The LC50 values for 96 h were 3.88 ppm. The LT50 time at 4 and 8 ppm levels of m-cresol were 112 00', 29 55', respectively.
Keywords: acute toxicity; m-cresol; Oncorhynchus mykiss; rainbow trout